The Pattern of Austrian Dairy Farm Household Strategies - Monika Krammer; Manuela Larcher; Stefan Vogel; Erwin Lautsch (German Journal of Agricultural Economics (GJAE), 2012)
Developments in the agriculture sector, such as the European Union (EU) Common Agricultural Policy reforms and the increasing volatility of the markets due to liberalisation processes, pose far-reaching challenges to farm household development, and especially the most affected sectors, such as dairy farming. It is assumed that individual farmers develop strategic approaches to their future farming activities (farm household strategies) in order to react to these developments. This involves reconsidering existing approaches and developing new strategies, both on and off the farm. In order to evaluate these developments, it is necessary to first evaluate the current pattern of farm household strategies. This paper identifies and examines the farm household strategies of Austrian dairy farmers in order to better understand farm household development. Secondary data analyses on the basis of a survey of Austrian dairy farms conducted by the Federal Institute of Agricultural Economics Vienna provided the required information for the em-pirical identification of various types of farm household strategy. The analyses revealed a pattern of six types of farm household strategy within Austrian dairy farms: (1) genuine specialisation, (2) concentration, (3) horizontal diversification, (4) lateral diversification, (5) stable reproduction, and (6) disengagement. The study underlines the significance of socio-economic as well as demographic and farm characteristics which were used to identify and describe types of farm household strategy.
Keywords: 330; Milchviehhaltung; Wirtschaftliche Anpassung; Österreich